Internalization of Religious Moderation Values Through Madrasah Culture: Fostering Tolerance and Wisdom - Siswanto, Muhamad (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
Indonesia, as a country rich in ethnic, religious, racial, and cultural diversity, faces challenges in maintaining harmony among its various groups. Religious moderation serves as a vital solution to foster a harmonious society by promoting a balanced approach to practicing religious teachings, respecting differences, and avoiding extremism. Madrasahs, as Islamic educational institutions, play a strategic role in internalizing the values of religious moderation through a culture that emphasizes compassion, peace, and tolerance. This study uses a qualitative method with a literature review approach. The findings reveal that madrasah culture plays a key role in instilling the values of religious moderation in students by creating an inclusive environment that respects diversity. Through a religion-based approach that highlights tolerance, madrasahs can nurture a generation capable of facing social diversity with openness and acceptance. This education focuses not only on theoretical knowledge but also on the practical application of these values in everyday life. Fostering tolerance and wisdom in dealing with differences is crucial in Indonesia’s multicultural society. Therefore, the implementation of religious moderation within the curriculum and activities of madrasahs—through a comprehensive approach involving all school elements, including teachers and students—serves as an effective strategy to create a generation that is not only religiously literate but also capable of living harmoniously within social diversity.